Restaurant attributes on customer satisfaction and behaviour intention: a case study of San Francisco Coffee / Ahmad Azwan Mohamad Fakhrur - Mohamad Fakhrur, Ahmad Azwan (2016)
San Francisco Coffee is a local gourmet coffee joint and a direct competitor to international coffee joint such as Starbucks and Coffee Bean. They are sharing a similar business model and were established within the same time frame. However, San Francisco Coffee is the slowest in terms of business location and sales revenue. One finding stated that San Francisco Coffee was the less preferred coffee joint by the customers. The aim of this study is to identify the attributes that lead to customer satisfaction and their behavioural intention to the restaurant attributes in San Francisco Coffee and how these attributes have an effect on customer satisfaction and behavioural intention. Pearson Correlation and Multiple Regression were used in getting more insight of the relationship. Findings showed the restaurant attributes has a positive relationship to customer satisfaction and behavioural intention. The findings would certainly help San Francisco Coffee and other coffee joint operators to plan on new strategies which can help in increasing the level of customer satisfaction and to bring out positive behavioural intention.